The influence of temperature on viscoelastic friction properties. (August 2016) - Putignano, C.; Reddyhoff, T.; Dini, D.
Abstract: Viscoelastic friction strongly depends on temperature, which determines the material stiffness and, therefore, given a constant load, the volume that is deformed and dissipates energy. We compare the results obtained by a numerical approach introduced by Carbone and Putignano (2013)[1] with measurements that separate viscoelastic losses from Coulomb contribution. This is done for a range of temperatures. We show that viscoelastic friction curves for different temperatures can be arranged into a single master curve using a frequency shift coefficient, which can be found from the characterization of the viscoelastic material response. This shows that it is possible to accurately (a) use dynamic material analysis data to extrapolate viscoelastic friction measurements to values outside the tested range, and (b) use a tribometer to obtain fundamental viscoelastic material properties. Abstract : Highlights: Experimental protocol to separate viscoelastic losses from other friction sources. Validation of Carbone & Putignano's (2013) BE method for range of temperatures. Viscoelastic friction at different temperatures collapses onto a single master curve. Outcome: DMA data may extrapolate viscoelastic friction outside the tested range. Outcome: Tribometers can measure fundamental viscoelastic material properties.